RISK FACTORS OF OPPORTUNISTIC INFECTIONS IN CHILDREN WITH PARENTERAL HIV INFECTION - V.B. Denisenko; E.N. Simovanyan ("Paediatrician" Publishers LLC, 2011)
High incidence and unfavorable clinical course of opportunistic infections in children with HIV-infections lead to the study of risk factors of their development. Objective: to reveal risk factors of local and generalized opportunistic infections in children with parenteral HIV-infection. Methods: at the first stage of a study, risk factors of local opportunistic infections starting in 12 months after parenteral HIV-infection were retrospectively estimated in 98 children. At the second stage, prospective observation during 120 months with analysis of risk factors of generalized opportunistic infections was performed. Results: local opportunistic infections were detected in 41% of patients in 12 months after HIV-infection. Independent predictors of their development were infantile age at the moment of HIV-infection (OR 3.7; 95% CI 1.0-13.2) and acute HIV-infection (OR 4.4; 95% CI 1.3-15.1). Generalized opportunistic infections were detected in 46% of patients during 120 months of observation. Independent risk factors of generalization were the presence of local opportunistic infection in medical history (OR 2.7; 95% CI 1.2-6.1), delay of physical development > 10% (OR 4.2; 95% CI 1.4-12.8) and the level of CD4+ lymphocytes < 15% at the time of initial examination (OR 46.1; 95% CI 9.9-213.1). Conclusion: authors demonstrated the significance of clinical and laboratory tests of immune system and virus replication intensity for the prognosis of development of local and generalized opportunistic infections in children with HIV-infection.Key words: children, HIV-infection, opportunistic infection, risk factors.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (3): 48-54)